TURNITIN WASHBACK EFFECT: EFL STUDENTS’ METHODS OF AVOIDING PLAGIARISM ON ACADEMIC WRITING - Utami, Westi Haryanti (Jurnal Pendidikan Bahasa dan Sastra, 2019)
Academic dishonesty is a major issue in the current educational problem, especially in academic writing. One of the most crucial practices of academic dishonesty is plagiarism. In order to prevent it, many universities worldwide use Turnitin as one of the plagiarism detection software for the solution to fighting plagiarism. Therefore, this study aimed to identify the methods used by English as Foreign Language (EFL) students in avoiding plagiarism on their academic writing. A case study at a university in Indonesia was conducted. Six postgraduate students of English Education major were chosen as the participants to be interviewed regarding the utilization of Turnitin. From the students’ responses, in avoiding plagiarism, they get the idea to write from observing their surroundings, following their passion and reading a lot. Moreover, in the process of writing academically from sources, they also employ patchwriting, citing the sources correctly, self-reading, re-checking the sources, checking to other plagiarism detection software and learning about Turnitin. However, in order to decrease the similarity percentage of their papers, they were also deleting the similar-detected part and even changed the paper. Therefore, it is recommended for the students, teachers, and institutions to concern more on how to write from sources as the part of learning to write rather than rely too much on the originality report from Turnitin.